2022
DOI: 10.46306/lb.v3i1.110
|View full text |Cite
|
Sign up to set email alerts
|

Systematics Literature Review: Eksplorasi Etnomatematika Pada Aktivitas Masyarakat

Abstract: Ethnomathematics is mathematics that grows, develops and is practiced by cultural groups such as urban and rural communities, children of certain age groups, labor groups, indigenous peoples, and others. Ethnomathematics that links culture, one of which is community activity and mathematical concepts, certainly has mutually supportive characteristics. This paper discusses the review of results from several journals to obtain information on the application of ethnomathematics to community activities. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Di Indonesia telah banyak kajian etnomatematika oleh para peneliti karena matematika berperan penting dalam kehidupan (Andriono, 2021;Astriandini & Kristanto, 2021;Fadlilah et al, 2015;Irsyad et al, 2020;Nova & Putra, 2022;Putri, 2017;Septianawati et al, 2019;Sitti Fatimah S. Sirate, 2015;Sudihartinih, 2020;Suriati & Firdaus, 2019;Wahyudi & Putra, 2022;Zaenuri & Dwidayati, 2018). Etnomatematika sebagai suatu pendidikan matematika yang mengintegrasikan nilai-nilai kultur dalam pembelajaran matematika perlu menggagas integrasi secara nyata nilai-nilai kultur tersebut (Sitti Fatimah S. Sirate, 2015).…”
Section: Pendahuluanunclassified
“…Di Indonesia telah banyak kajian etnomatematika oleh para peneliti karena matematika berperan penting dalam kehidupan (Andriono, 2021;Astriandini & Kristanto, 2021;Fadlilah et al, 2015;Irsyad et al, 2020;Nova & Putra, 2022;Putri, 2017;Septianawati et al, 2019;Sitti Fatimah S. Sirate, 2015;Sudihartinih, 2020;Suriati & Firdaus, 2019;Wahyudi & Putra, 2022;Zaenuri & Dwidayati, 2018). Etnomatematika sebagai suatu pendidikan matematika yang mengintegrasikan nilai-nilai kultur dalam pembelajaran matematika perlu menggagas integrasi secara nyata nilai-nilai kultur tersebut (Sitti Fatimah S. Sirate, 2015).…”
Section: Pendahuluanunclassified
“…Ethnomathematics is a variety of outputs of mathematical activities that are owned or developed in the community, including mathematical concepts, for example, on cultural heritage in the form of temples and inscriptions (Puspitasari & Putra, 2022), pottery and traditional tools (Hafifah & Putra, 2021;Amanda & Putra, 2022), batik and embroidery motifs (Yolanda & Putra, 2022;Delviana & Putra, 2022), and local units. Many researchs also show that there are mathematical activities in several aspects of culture like folklore (Nova & Putra, 2022), traditional musical instruments (Adawiah & Putra, 2022), traditional ceremonies (Wahyudi & Putra, 2022), traditional houses (Nurfauziah & Putra, 2022), traditional culinary (Fitriani & Putra, 2022), and traditional games (Zayyadi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The opinion of Wahyuni et al (2013) revealed that one thing that can be a bridge between education and culture, especially mathematics education, is ethnomathematics (Wahyuni et al, 2013). Ethnomatematics is mathematics that grows and develops in a particular culture (Dhiki & Bantas, 2021).…”
Section: Introductionmentioning
confidence: 99%